ANALISIS BIOFISIK KAWASAN JEMBATAN NASIONAL SURAMADU SISI MADURA BERBASIS SISTEM INFORMASI GEOGRAFIS DAN PENGINDERAAN JAUH UNTUK PERTANIAN - Eko Murniyanto; Zainul Hidayah; Wahyu Andy Nugraha (Universitas Trunojoyo Madura, 2010)
This research aimed to identify biophysics, development of spatial data base contained information of biophysics condition and also biophysics potency mapping in Suramadu Bridge Surroundings area. This biophysics research was located in the Suramadu Bridge area especially in Bangkalan side with area more or less about 600 hectare using information geographic systems and remote sensing application. Result of land suitability evaluation for agricultural land showed that there is no study area has very suitability for become agricultural land. The highest rank was only fairly suitable which is Burneh, Masaran, Petapan and Markopek Village. Meanwhile, other village such as Sendang Daya, Pangpong and Sukolilo Barat was not suitable for agriculture.